Modeling Cellular Systems - Graw, Frederik; Matthäus, Franziska; Pahle, Jürgen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This contributed volume comprises research articles and reviews on topics connected to the mathematical modeling of cellular systems. These contributions cover signaling pathways, stochastic effects, cell motility and mechanics, pattern formation processes, as well as multi-scale approaches. All authors attended the workshop on "Modeling Cellular Systems" which took place in Heidelberg in October 2014. The target audience primarily comprises researchers and experts in the field, but the book may also be beneficial for graduate students.
Numerical treatment of the Filament Based Lamellipodium Model (FBLM) -- Understanding the role of mitochondria distribution in calcium dynamics and secretion in bovine chromaffin cells -- IL-2 stimulation of regulatory T cells: a stochastic and algorithmic approach -- Spatio-Temporal Modeling of Membrane Receptors -- Distribution approximations for the chemical master equation: comparison of the method of moments and the system size expansion -- Dynamical features of the MAP kinase cascade -- Sampling from T cell receptor repertoires.
Keywords: Biomedical engineering; Biomathematics; Bioinformatics; Neural networks (Computer science) .; Biomedical Engineering and Bioengineering; Mathematical and Computational Biology; Computational and Systems Biology; Mathematical Models of Cognitive Processes and Neural Networks